Nutritional attitudes of professional women volleyball players: a cross-sectional study from Türkiye - Sahin, O.; Sahiner Guler, V.; Turan, M. B.; Yoka, K.; Yoka, O.; Polat, Y. (Frontiers in Nutrition, 2025)
Background: Nutritional habits are a critical factor influencing the performance and recovery of professional athletes. Understanding how demographic variables affect nutrition-related attitudes is essential for developing targeted interventions.